Strategi Pengembangan Usaha Pembenihan Ikan Nila di Balai Benih Ikan (BBI) Lokal Gunung Manau Kecamatan Batuman di Kabupaten Balangan - Arief Hidayatullah; Hairun Hairun (Rawa Sains: Jurnal Sains STIPER Amuntai, 2019)
The research aims to identify internal and external factors, formulate alternative strategies, and prioritize strategies in developing the tilapia hatchery business at the Gunung Manau Local Fish Breeding Center, Batumandi District, Balangan Regency. The basic method used is descriptive method and carried out by survey techniques. The data used in this study are primary and secondary data. Data analysis methods used (1) SWOT Analysis, (2) IE and SWOT matrix (3) QSP matrix. The results of the study reveal that (1) the main underlying strength is easily accessible production facilities, (2) the main disadvantage is that marketing outside the region is still lacking. (3) The main opportunity to get assistance from the government. (4) Whereas the fundamental threat is the effect of the dry season. (5) Based on the IE matrix, the strategy is market penetration and product development. (6) The results of the SWOT matrix from the alternative strategies implemented are maintaining seed quality and increasing production through increased application of Standard Operating Procedures (SOP), Utilization of feed probiotic processing technology and feed training and increasing the number, improving the performance of technical officers in managing business seeding by providing encouragement, monitoring and evaluation as well as cooperative relations of the related institutions. (7) The priority strategy that can be applied is to improve the performance of technical officers